2012
DOI: 10.1111/ijcp.12064
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and associated cardiovascular risk factors in the State of Kuwait: the first national survey

Abstract: This study found that advancing age (≥ 40 years), diabetes mellitus, obesity, positive family history of diabetes, hypertension and dyslipidaemia are significant risk factors for developing CVD in Kuwait as in other parts of the world. Understanding these factors allows for preventive measures to be taken for Kuwaiti population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
2
19
2
1
Order By: Relevance
“…A previous study examining CV risk factors in Kuwait found prevalence of dyslipidemia to be lower at 73% [17]. However, outpatients in the previous study were aged between 20–65 years; higher prevalence in the present study may be due to the inclusion of outpatients over 65 years of age.…”
Section: Discussioncontrasting
confidence: 68%
“…A previous study examining CV risk factors in Kuwait found prevalence of dyslipidemia to be lower at 73% [17]. However, outpatients in the previous study were aged between 20–65 years; higher prevalence in the present study may be due to the inclusion of outpatients over 65 years of age.…”
Section: Discussioncontrasting
confidence: 68%
“…Due to sharing common culture, religion, language, life style, foods (e.g. no alcohol consumption) and the prevalence of metabolic diseases [29,30], the outcomes of this study can be useful and applicable to other neighboring countries in the Middle East including Arabian Gulf countries. The main limitation of the study was the relative small number of subjects involved after partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and four articles were identified in PubMed, and 32 articles [16, 17, 1924, 26, 28, 3051] remained after exclusion of nonepidemiologic studies based on title and abstract review. One additional article [52] was identified through personal communication and 5 articles [18, 25, 27, 29, 53] and one survey report [54] through other database searches leading to a total of 39 articles. Of the 39 epidemiology articles identified, 4 articles [40, 48–50] could not be retrieved and a total of 17 were excluded after full-text review for the following reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 39 epidemiology articles identified, 4 articles [40, 48–50] could not be retrieved and a total of 17 were excluded after full-text review for the following reasons. The excluded articles included two review studies [16, 17], one letter to editor [39], one study with self-reported BMI [36], one study that reported body weight but not height [51], one study that focused on anthropometric measures other than BMI [41], and eleven studies [37, 38, 4247, 52–54] because of data overlap or redundancy. From among all studies with data overlap or redundancy, we selected the study reporting the most detailed results [19, 20, 2224, 33, 35].…”
Section: Resultsmentioning
confidence: 99%